ANALISIS BIAYA DAN PENANGANAN LOKASI RAWAN KECELAKAAN AKIBAT KECELAKAAN LALU LINTAS DI KOTA DENPASAR - I.G.A Putri Adnya Swari; P. Alit Suthanaya; I.N. Widana Negara (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2014)
Denpasar city has a traffic accident rate is high compared to most other regions. Contributing factor is the traffic condition, which is an accumulation of traffic conditions the interaction of the various characteristics of driver, vehicle, road infrastructure and environmental characteristics. By that condition, it needs an effort to identify the black site, black spot, the cost of accidents and treatment efforts to reduce traffic accidents. The research has used secondary data from local police department as an accident data from 2007 until 2011 and survey’s data on the location. Of which data continue to be analyzed with the number of accident to find out the black site with Z-score method and to determine the black spot with cusum method. While the analysis of accident cost using the method of Gross Output (Human Capital). In restraining accident, a research should be done to identify causing accident factors. Based on analysis of black site obtained that the lines of the street in denpasar as an black site is on quadrant A, consisting of Ngurah Rai By pass line, Gatot Subroto and Imam Bonjol lines. The Cusum determination done to identify the location of black spot found on Ngurah Rai Bypass street Sta 8 - Sta 9 with cusum score 12,938.The cost of accident victims and accident costs were highest in 2011 in the amount of 36.988.633.141/year and 81.267.473.411/year. Recommendation from the research is that government should observe safety factors for the roadway users with put in traffic sign and the other safety facilities on research areas which has black spot.